Is monetary poverty a suitable proxy for deprivation in the physical environment? - Notten, G (Université d'Ottawa | University of Ottawa, 2009)
The multidimensional nature of poverty has long been acknowledged; even persons with sufficient financial resources may be unable to achieve satisfactory levels of well-being in other dimensions. However, traditional financial poverty analyses still play a predominant role in the formulation of poverty reduction strategies. In this paper we analyze the consequences of using financial poverty as a proxy for deprivation in the physical environment of children in the Republic of Congo by studying the degree of overlap between these dimensions. Our results indicate that incidence rates of poverty and deprivation differ substantially in magnitude; that high risk poverty characteristics do not necessarily correspond to high risk deprivation characteristics; and that the relation between poverty and deprivation in the physical environment is positive but not very strong. We conclude that using financial poverty indicators seems to be a blunt tool to identify vulnerable groups in the physical environment dimensions.
Keywords: financial poverty; deprivation; water and sanitation; housing; integration; Republic of Congo